Longitudinal association of breakfast and midnight snacks with depressive symptoms in China multi-ethnic adolescents - Xu, Honglv; Zhang, Gaohong; Liu, Zihan; Xue, Xiaolu; Hu, Dongyue; Yang, Jieru; Jia, Jing; Zhang, Xuemei (Frontiers in Psychiatry, 2025)
IntroductionStudies have suggested a link between dietary behavior and adolescent depressive symptoms, but longitudinal data are scarce. This study examines the longitudinal association of breakfast and midnight snacks consumption with depressive symptoms among multi-ethnic adolescents in China.MethodsFrom October 2022 to October 2024, 1,693 middle school students (52.3% females) from Yunnan Province participated in five follow-up surveys (T1-T5) conducted every six months. Breakfast and midnight snacks consumption were assessed using questionnaires, and depressive symptoms were measured using Children’s Depression Inventory. The latent growth curve model was analyzed using Mplus software to assess the potential growth trajectories of breakfast days, midnight snacks days, and depressive symptom scores across five time points. The generalized estimation equation model was applied to examine the association between the number of breakfast and midnight snacks days and depressive symptom scores. Two models were established: Model 1 was unadjusted, without controlling any variables; Model 2 was adjusted for demographic variables and other potential confounders influencing depressive symptoms. A restricted cubic spline analysis was used to examine the relationship between the number of breakfast days per week, midnight snacks days per week, and depressive symptoms.ResultsThe prevalence of depressive symptoms increased from 26.3% at T1 to 37.3% at T5 (P < 0.01). After adjusting for confounders, breakfast frequency (β = -0.71, 95%CI: -0.87-0.56) and midnight snacks frequency in males (β = 0.39, 95%CI: 0.24 - 0.55) and females (β = -0.77, 95%CI: -0.92 - -0.63; β = 0.17, 95%CI: 0.02 - 0.32) were associated with depressive symptoms (all P < 0.05). Males eating breakfast and midnight snacks fewer than three days and more than four days, respectively, per week, and females eating breakfast and midnight snacks fewer than four days and more than two day, respectively, per week, had an increased risk of depressive symptoms.DiscussionSkipping breakfast and eating midnight snacks are related to depressive symptoms in multi-ethnic Chinese adolescents. Addressing unhealthy eating behaviors is critical for preventing and mitigating adolescent depressive symptoms.